2010
DOI: 10.1001/archneurol.67.6.670
|View full text |Cite
|
Sign up to set email alerts
|

Nonmotor Symptoms in Genetic Parkinson Disease

Abstract: To review current knowledge on nonmotor symptoms (NMS), particularly psychiatric features, in genetic Parkinson disease (PD) and to provide original data for genetic and idiopathic PD. Data Sources: A MEDLINE search using Parkinson and known PD genes focused on the presence of depression, anxiety, hallucinations, and dementia was performed. Original data from 82 outpatients with idiopathic (n=55) and genetic (n= 27) PD were obtained. Study Selection: All studies including information on NMS and patients with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 27 publications
3
46
1
Order By: Relevance
“…Sex differences in other genes associated with PD have been examined in a small study of LRRK2, parkin, AT-P13A2, and PINK1 mutations (n 5 27) in the context of nonmotor signs and found that 48% were men. 31 However, in a larger study of GBA and parkin that included heterozygote carriers, 32 the sex distribution was similar to idiopathic PD.…”
Section: Resultsmentioning
confidence: 92%
“…Sex differences in other genes associated with PD have been examined in a small study of LRRK2, parkin, AT-P13A2, and PINK1 mutations (n 5 27) in the context of nonmotor signs and found that 48% were men. 31 However, in a larger study of GBA and parkin that included heterozygote carriers, 32 the sex distribution was similar to idiopathic PD.…”
Section: Resultsmentioning
confidence: 92%
“…All of the therapeutic approaches outlined above aim at treating the dopaminergic motor symptoms of PD, which remain the current focus of therapy development. However, it is clear that PD pathology extends far beyond the dopaminergic nigrostriatal system, and that nonmotor symptoms such as cognitive impairment, dementia, depression, psychosis, and autonomic dysfunction significantly contribute to the complex battery of deficits PD patients face, even at early stages of the disease (Chaudhuri et al, 2006(Chaudhuri et al, , 2011Chaudhuri and Schapira, 2009;Kasten et al, 2010;Lim and Lang, 2010;Poewe, 2010;Wood et al, 2010;Bassetti, 2011) (Table 3). Because most of these symptoms do not respond to, but are often exacerbated by, the traditional dopamine replacement therapy and STN DBS, the development of pharmacotherapy that could alleviate these nonmotor symptoms, while being effective in reducing parkinsonian motor signs, represents one of the most important challenges both basic and clinical PD scientists may face in the years to come.…”
Section: /1989mentioning
confidence: 99%
“…In prior studies covering the EU-5 nations, reported rates of hallucinations and delusions among patients with PD ranged from 10-45% in France, [34][35][36] 13-29% in Germany, 37,38 11-32% in Italy, [39][40][41] 15-42% in Spain 42,43 and 13-55% in the UK. 17,[44][45][46] These broad reported ranges highlight the difficulty of carrying out cross-study comparisons.…”
Section: Disruptiveness and Comorbidity Ratesmentioning
confidence: 99%